A patient-reported outcome measures-based composite index (RAPID3) for the assessment of disease activity in ankylosing spondylitis - Cinar, Muhammet; Yilmaz, Sedat; Cinar, Fatma Ilknur; Koca, Suleyman Serdar; Erdem, Hakan; Pay, Salih; Simsek, Ismail (Springer Heidelberg, 2015)
A single questionnaire regarding to disease activity for all rheumatic diseases may present advantages to introduce quantitative measurement into routine care. The aim of this study was to evaluate the correlation of routine assessment of patient index data 3 (RAPID3) with Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Ankylosing Spondylitis Disease Activity Score (ASDAS). A total of 341 consecutive AS patients who met the modified New York classification criteria were included. All patients completed BASDAI and RAPID3 at each visit, and their physicians completed physician global assessment. ASDASs were calculated using defined formulas. Proposed RAPID3 severity categories were compared to BASDAI and ASDAS categories. Spearman's rho correlation test and kappa statistics were used to analyze statistical significance. The median age of AS patients was 34.0 (21.0-69.0) years and the median disease duration 10.0 (2.0-35.0) years. Median scores for RAPID3, BASDAI, ASDAS-CRP, and ASDAS-ESR were 13.0 (0.0-27.3), 4.7 (0.0-9.7), 3.0 (0.4-5.8), and 2.5 (0.5-6.3), respectively. RAPID3 was strongly correlated with BASDAI and ASDAS-ESR (r = 0.842, r = 0.815; p < 0.001, respectively). Among the 209 patients with high disease activity according to BASDAI, 83.3 % had high or moderate severity according to RAPID3 (kappa 0.693; p < 0.001). Among the 133 patients with moderate, high, and very high disease activity on ASDAS-CRP, 91.7 % had high or moderate severity according to RAPID3 (kappa 0.548; p < 0.001). RAPID3 is as informative as BASDAI and ASDAS in our cohort of AS patients. We therefore suggest that RAPID3 may be used to assess the patient status quantitatively in AS patients, as part of routine care.
Keywords: Ankylosing spondylitis; Disease activity; RAPID3; ASDAS; BASDAI